(untitled) (Research, Society and Development, 2022)
Child psychopathy is a phenomenon of the human mind that instigates many concerns about this theme, and it is still difficult to precisely define the manifestation of this disorder in children and only identifying possible personality traits. Thus, the study aimed to identify the traits of psychopathy in child development, in addition to understanding the rules adopted with these children. This is an integrative review research. Data were selected through an electronic search in the following databases: Latin American and Caribbean literature on Health Sciences (LILACS via BVS), US National Library of Medicine (PUBMED) and Scientific Electronic Library Online (SCIELO), in the period of 2010 until October 2021. With the results obtained from a sample of 9 studies, it was found that despite the diagnosis of psychopathy being made in adulthood, it is possible to identify and monitor traces of psychopathy in early childhood, which are more present in conduct disorders, antisocial and developed by maltreatment and physical violence during childhood. It is concluded that it is important to analyze the behaviors of children who present the traits of a psychological disorder and to develop new instruments to help in the early identification of this psychopathology.